Feeding habits of Molina´s hog-nosed skunk in Pampas Grassland of Argentina - Castillo, Diego Fabian (2014)
We studied the feeding ecology of Molina´s hog-nosed skunk (Conepatus chinga) in a protected area of the Pampas grassland by comparing the content of scats (140 samples) to prey abundance (estimated by invertebrate capture rates from 38 pitfall trap grids). Fecal analysis supported a largely insectivorous diet, with small vertebrates and carrion representing minor alternative resources. Almost all invertebrate prey was significantly more abundant in the warm period than the cold period, whereas skunk diet did not vary seasonally. Even though Molina?s hog-nosed skunks were considered to be opportunistic foragers due to their wide trophic niche, our results indicate that despite their trophic generalism, they consumed several prey items in proportions differing from those expected by their respective availabilities.